Gender and food from production to consumption and after. - Segal, Marcia Texler, 1940-; Demos, Vasilikie P. (Bingley, U.K. : Emerald, 2016)
Volume 22 explores the complex relationships between gender and food in a variety of locations and time periods using a range of research methods. Authors show that gender inequality and mens dominance are implicit or explicit, and that in times of both stability and change, the burden of many if not most aspects of food production and provisioning falls upon women and is an integral part of the care work they perform. Food is shown to be related to societal structures of power, resources and labor markets, as well as households, bodies and emotions. Health, well-being and sustainability emerge as major tropes in the economic and geographic north and south from the arctic to the equator and places between. Western cultural trends regarding specialized diets as they relate to health and illness are examined from a gender lens as is childrens nutrition worldwide. Gender inequality as it affects the struggle for access to land, the affordability of food, and its nutritional value is identified as a major social policy issue.
Three sisters from the outer boroughs: class, reproduction, and food in the early 1940s through the mid-1950s / Roberta Spalter-Roth -- Food trends through two generations amongst Saami in Arctic Fennoscandia / Myrdene Anderson -- Traditional provisioning responsibilities of women in Northern Ghana / Eileen Bogweh Nchanji, Imogen Bellwood-Howard -- Access to opportunity: a case study of street food vendors in Ghana's urban informal economy / Arianna King -- From unhealthy satiety to health-oriented eating: narratives of the Mediterranean diet, managing a chronic illness / Franca Bimbi -- Empowering women, strengthening children: a multi-level analysis of gender inequality and child malnutrition in developing countries / Rebekah Burroway -- Gluten-free eating and gendered feeding work in families affected by celiac disease / Denise A. Copelton -- Women's income and healthy eating perception / Antonella Samoggia, Aldo Bertazzoli, Vaiva Hendrixson, Maria Glibetic, Anne Arvola -- Emotional labor, food provisioning and local food system engagement / Rebecca L. Som Castellano -- The culinary <U+201c>food chain<U+201d>: private and personal chefs negotiate identity and status in the culinary profession / Alexandra Hendley -- The physical and emotional contours of feeding labor by school food service employees / Ashley D. Vancil-Leap -- Subversive cooking in liberal feminism, 1963-1985 / Stacy J. Williams.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Gender Studies; Gender studies: women; Food & society; Women's studies; Food habits